Individual Fund Manager Sentiment, Fund Performance and Performance Persistence - Fu, Ying-Fen (International Journal of Economics and Financial Issues, 2014)
This study contributes to the literature by examining the relation among fund performance, performance persistence and individual fund manager sentiment, rather than the fund industry sentitment. This study employs the turnover rate as the proxy of individual fund manager sentiment. Using the one and two-way sorting methods and the panel data regression analysis, this study finds that the equity funds in Taiwan have performance persistence in the both short and long run. We find the funds with a higher turnover rate (i.e., higher fund managers’ sentiment) perform better no matter they are in the winner or loser groups. This phenomenon persists both in the short- and long-terms, which implies the influence of sentiment on the performance is persistent. The investors should choose winner funds due to their persistence, and choose those whose turnover rate is in top 40% of the winners. Keywords: fund performence; performence persistence; sentiment JEL Classifications: G11; G19; G23